Aplikasi Google Maps API untuk Sistem Informasi Geografis - Muhammad Sholeh; Naniek Widyastuti; Ali Mashuri (JUITA : Jurnal Informatika, 2011)
Presentation of the current information system does not just display text-based information, but it can display images in the form of geography. With a view shaped geography will certainly make easier the users in accessing information, especially information relating to an area / region. Information of university is one of very important information for users who want to know abaut it. For information displayed interesting, geography-based information system support must be very profitable users. With this geographic-based information system, users can view the location of a university in the form of maps and routes that can be passed to get to the location of the campus. In this paper developed a geographical information system, especially information on universities in the region Kopertis V Yogyakarta. Applications developed using the web server Apache 2.2.6, PHP 5.2.5, MySQL 5.0.51 and using google maps API